Pressure transient suppression in drainage systems of tall buildings. Issue 4 (19th May 2019) - Gormley, M.; Kelly, D. A.
ABSTRACT: The suppression of pressure transients in building drainage systems is essential for reducing cross-contamination by the spread of pathogens. The topic is now much better understood due to work following the invention of the first drainage-specific positive-pressure transient-attenuation device in the year 2000. The present research addresses the attenuation of much larger problematic air-pressure transients found in tall buildings. The development of a new technique is described for the attenuation of positive air pressure transients of approximately 2000 mm water gauge (wg) (20 kPa) for which there is currently no means to alleviate. The performance of the new technique was validated by numerical simulation and full-scale test-rig experiments. The full-scale test rig represented a 44-storey building with a 150 mm main drainage stack. The pressure wave generator applied a 2000 mm wg pressure transient from a large accumulator compressor delivering 270 litres of air at 10 bar pressure. This resulted in a capacity of 2700 litres of air at atmospheric pressure delivered into the system within 0.2 s. Results show that a prototype device using the new technique is capable of reducing the applied pressure transient by 88%, rendering it harmless and returning the system to normal operation in a matter of seconds.